Kesiapan Psikologis Ibu Hamil Trimester III Dalam Persiapan Persalinan Pasca Relaksasi Hypnobirthing - Henik Istikhomah; Dyah Ayu Putri Mumpuni (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Psychological Readiness Pregnancy Trimester III, Post-Relaxation Hypnobirthing. A number of fear seen in pregnant women during the third trimester. Unpreparedness to face the birth mother to be one of the causes of high maternal mortality rate. Mother began to feel fear of pain and the physical dangers that will arise at the time of delivery. Because they were, the mother must make themselves maintain the harmony of mind and body through relaxation. Hypnobirthing techniques can help relax the muscles so that mothers avoid the anxiety and may help mothers more calm in the face of labor. The purpose of this study to describe the psychological readiness of third trimester pregnant women in childbirth after relaxation hypnobirthing. Quantitative descriptive research. The population in this study is the third trimester pregnant women who have followed the relaxation hypnobirthing ≥ 4 times in BPM and BPM Yessi Yosi Trihana Aprilia Klaten. Saturated sampling technique is sampling as many as 30 third trimester pregnant women who had attended relaxation hypnobirthing ≥ 4 times as respondents. Of the 30 respondents third trimester pregnant women who attended ≥ 4 times showed 19 respondents (63.30%) declared ready psychologically to face childbirth after following the relaxation of hypnobirthing ≥ 4 times. And 11 respondents (36.70%) are not ready psychologically to face the post-relaxation hypnobirthing childbirth ≥ 4 times. Most of the third trimester pregnant women are better prepared psychologically to face childbirth after following the relaxation of hypnobirthing ≥ 4 times in BPM and BPM Yessi Yosi Trihana Aprilia Klaten.